CAMK1D Inhibits Glioma Through the PI3K/AKT/mTOR Signaling Pathway - Jin, Qianxu; Zhao, Jiahui; Zhao, Zijun; Zhang, Shiyang; Sun, Zhimin; Shi, Yunpeng; Yan, Hongshan; Wang, Yizheng; Liu, Liping; Zhao, Zongmao (Frontiers in Oncology, 2022)
Calcium/calmodulin-dependent protein ID (CAMK1D) is widely expressed in many tissues and involved in tumor cell growth. However, its role in gliomas has not yet been elucidated. This study aimed to investigate the roles of CAMK1D in the proliferation, migration, and invasion of glioma. Through online data sets, western blot, and immunohistochemical analysis, gliomas tissue has significantly lower CAMK1D expression levels than normal brain (NB) tissues, and CAMK1D expression was positively correlated with the WHO classification. Kaplan-Meier survival analysis shows that CAMK1D can be used as a potential prognostic indicator to predict the overall survival of glioma patients. In addition, colony formation assay, cell counting Kit-8, and xenograft experiment identified that knockdown of CAMK1D promotes the proliferation of glioma cells. Transwell and wound healing assays identified that knockdown of CAMK1D promoted the invasion and migration of glioma cells. In the above experiments, the results of over-expression of CAMK1D were all contrary to those of knock-down. In terms of mechanism, this study found that CAMK1D regulates the function of glioma cells by PI3K/AKT/mTOR pathway. In conclusion, these findings suggest that CAMK1D serves as a prognostic predictor and a new target for developing therapeutics to treat glioma.